Stroke Mimicry in Neuro-Oncology Evaluating the Frequency, Mechanisms, and Outcomes of Brain Tumors Presenting as Acute Ischemic Stroke - Rashid Imran, Muhammad Imran Khan, Adnan Mahmood, Muhammad Jahangir Khan, Arwa Humayun, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Acute ischemic stroke is one of the most common neurological emergencies, yet a significant proportion of patients presenting with stroke-like symptoms are later diagnosed with alternative conditions, known as stroke mimics. Objective: To evaluate the frequency, mechanisms, and outcomes of brain tumors presenting as acute ischemic stroke and to identify predictors of tumor-related stroke mimicry. Methodology: This cross-sectional observational study was conducted at Department of Neurology, Punjab Institute of Neurosciences Lahore from 1st April 2023 to 30th September 2023. A total of 196 patients presenting with acute neurological deficits initially suspected to be ischemic stroke but subsequently diagnosed with brain tumors were included. Clinical data, risk factors, neuroimaging findings, tumor characteristics, and hospital outcomes were analyzed. Results: Majority of patients were males 60.2% with a mean age of 52.3±14.6 years. Hemiparesis (55.6%) and aphasia (27.6%) were the most common presenting symptoms, while seizures at onset occurred in 23.5% of cases. Peritumoral edema with mass effect (61.7%) and contrast enhancement (72.4%) were the most frequent imaging features, with restricted diffusion mimicking ischemia seen in 29.6%. High-grade gliomas (32.7%) and metastatic tumors (31.1%) were the leading tumor types. Misdiagnosis leading to thrombolysis occurred in 9.2% of patients, with 2.6% developing hemorrhagic complications. Overall, 11.2% of patients died during hospitalization, while 45.4% achieved favorable outcomes at discharge. Conclusion: Brain tumors are an important cause of stroke mimicry, often leading to misdiagnosis and inappropriate interventions. Clinical predictors such as younger age, seizures at onset, and absence of vascular risk factors, combined with careful interpretation of imaging, can improve diagnostic accuracy. Keywords: Stroke mimicry, Brain tumors, Acute ischemic stroke, Neuro-oncology, Seizures, Neuroimaging, Outcomes